2013
DOI: 10.1371/journal.pone.0068925
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse Imaging for Noninvasive Evaluation of Renal Parenchyma Elasticity: Preliminary Findings

Abstract: ObjectiveTo evaluate the diagnostic value of acoustic radiation force impulse (ARFI) to test the elasticity of renal parenchyma by measuring the shear wave velocity (SWV) which might be used to detect chronic kidney disease (CKD).Methods327 healthy volunteers and 64 CKD patients were enrolled in the study. The potential influencing factors and measurement reproducibility were evaluated in the healthy volunteers. Correlations between SWV and laboratory tests were analyzed in CKD patients.?Receiver-operating cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
141
9
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(180 citation statements)
references
References 35 publications
28
141
9
2
Order By: Relevance
“…linear increase of renal tissue elasticity associated with elevated urinary pressure [22,26]. Gender [21,34], race [27], weight or body mass index (BMI) [20], and also age [23,34,46] can modify the results in US elastography and several studies have found significant variations of renal parenchymal elasticity in these parameters [20,21,23,27,34,46].…”
Section: Ultrasound Elastography In Renal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…linear increase of renal tissue elasticity associated with elevated urinary pressure [22,26]. Gender [21,34], race [27], weight or body mass index (BMI) [20], and also age [23,34,46] can modify the results in US elastography and several studies have found significant variations of renal parenchymal elasticity in these parameters [20,21,23,27,34,46].…”
Section: Ultrasound Elastography In Renal Diseasesmentioning
confidence: 99%
“…In the native kidney, human studies have reported various markers associated with increased kidney stiffness: estimated glomerular filtrate rate (eGFR) [23,28,29], urinary albumin / creatinine or protein / creatinine ratio [30,33], serum creatinine [23,29], urea nitrogen [23], elasticity values in healthy native kidneys [23][24][25][26][27][28][29][30][31][32][33]35], kidney biopsies [25], other imaging tests etc [24,26,35]. Thus, there are studies finding no significant correlation between markers of chronic kidney injury and elasticity of renal parenchyma in native [27] or transplanted kidney [48,51], and also studies which could not prove a significant difference of elasticity between different stages of CKD [23,25]; in addition, it has been reported an increased intra-subject variability of results in CKD versus healthy controls [33] or a higher influence of arteriosclerosis markers, such as pulsatility index or resistivity index, on kidney stiffness than eGFR [28]. Such discrepancies may be explained not only by the heterogeneity of the markers utilized for the presence of fibrosis, by anatomic features of the kidney or by several confounders (age, BMI, technique variations etc), but also by the heterogeneity of primary kidney diseases which may be accompanied, in different stages of evolution, by inflammation, as it happens in the early phase of graft rejection or in vesicoureteral reflux.…”
Section: Evaluating Fibrosis In Native Kidney With Us Elastographymentioning
confidence: 99%
“…Despite these difficulties there are data showing a strong interobserver reproducibility of the method [12,13], making this non-invasive approach attractive for the assessment of renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…CKD is an important and costly health problem because of not only the increasing incidence and prevalence but also resulting in endstage renal failure. The progression of CKD shows fibrosis involving first glomeruli or interstitial space [15][16][17][18][19] . Fibrosis can be detected only by the biopsy procedure, which is interventional and non confortable for the patients.…”
mentioning
confidence: 99%